Current perspectives on invasive nontyphoidal Salmonella disease. Issue 5 (October 2017) - Haselbeck, Andrea H.; Panzner, Ursula; Im, Justin; Baker, Stephen; Meyer, Christian G.; Marks, Florian
Abstract : Purpose of review: We searched PubMed for scientific literature published in the past 2 years for relevant information regarding the burden of invasive nontyphoidal Salmonella disease and host factors associated with nontyphoidal Salmonella infection and discuss current knowledge on vaccine development. The following search terms were used: Salmonella, non typhoidal/nontyphoidal, NTS, disease, bloodstream infection, invasive, sepsis/septicaemia/septicemia, bacteraemia/bacteremia, gastroenteritis, incidence, prevalence, morbidity, mortality, case fatality, host/risk factor, vaccination, and prevention/control. Recent findings: Estimates of the global invasive nontyphoidal Salmonella disease burden have been recently updated; additional data from Africa, Asia, and Latin America are now available. New data bridge various knowledge gaps, particularly with respect to host risk factors and the geographical distribution of iNTS serovars. It has also been observed that Salmonella Typhimurium sequence type 313 is emergent in several African countries. Available data suggest that genetic variation in the sequence type 313 strain has led to increased pathogenicity and human host adaptation. A bivalent efficacious vaccine, targeting Salmonella serovars Typhimurium and Enteritidis, would significantly lower the disease burden in high-risk populations. Summary: The mobilization of surveillance networks, especially in Asia and Latin America, may provide missing data regarding the invasive nontyphoidal Salmonella disease burden and their corresponding antimicrobial susceptibility profiles. Efforts and resources should be directed toward invasive nontyphoidal Salmonella disease vaccine development.